Tradisi Sakura di Lampung: Representasi Hukum Islam dalam Kearifan Lokal Masyarakat Tanggamus - Arsyad, Mufid; Dimyati; Anggraini, Nike Ade (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to examine the representation of Islamic law in the Sakura tradition practiced in Tanggamus Regency, Lampung. The Sakura tradition is a festive cultural celebration among the indigenous Lampung community, characterized by the use of masks, changes in appearance, and culminating in a communal pole-climbing event known as beguai jejama. In the context of modernization, there has been a shift in the understanding of religious values embedded in this tradition, particularly among younger generations who are more exposed to popular culture. This research employs a qualitative approach with fieldwork methods, including participant observation, in-depth interviews, and document analysis. The main focus is on how values in Islamic law—such as justice, deliberation (musyawarah), and human rights—are integrated into the practice of the Sakura tradition. The findings reveal that although rooted in local culture, the Sakura tradition has strongly internalized Islamic values. Decision-making processes are conducted through deliberation, and community rights are respected, demonstrating a harmonious integration between customary law and Islamic law. Theoretically, this study highlights the importance of an integrative approach between Islamic law and local traditions in sustaining cultural practices and strengthening the legal identity of the community. With a wise and contextual approach, the Sakura tradition can continue to be preserved without contradicting Islamic teachings, serving as a medium for cultural da'wah and reinforcing social cohesion and interfaith harmony within a multicultural society.